IS A NEW EUROPEAN UNION ENERGY POLICY NEEDED? - Irina, PETRUCA (Strategii Manageriale)
In January 2009, because of a different between Russia and Ukraine, a major natural gas pipeline was closed, this being the worst gas cut-off of the decade. Eighteen countries have been interrupted from gas supplies and countries which had limited reserves and a shortage of alternative supply met a serious energy deficit, in the middle of an especially cold winter. After 22 days, the gas flows to all European countries were back to the normal level. A result of this, and of another similar dispute from 2006, was that the EU has put into question the confidence on the Russian gas supplies. The insecurity has led to a renewal of the political interest in energy security on EU level. The Russian cut-offs have been like a wake-up call to policy makers at a time when the EU faces significant energy security challenges as a result of the emerging world order. More than half of its energy, the EU buys from non-EU sources, while the demand for energy is always higher. In the meantime, the EU production levels of hydrocarbons are decreasing, leading to higher dependency on non-EU sources. Thereby, the energy security became a globally important topic and will raise important challenges for the EU in the future.